2020
DOI: 10.15275/rusomj.2020.0210
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent effect of deuterium depletion on tumor growth and metastasis

Abstract: Objective ― impact of different time regimens of deuterium depletion on progression of syngeneic grafted tumor in mice was investigated. Material and Methods ― Experiment was performed on 64 C57Bl/6 mice divided into two groups with substitution of regular water for deuterium depleted water: 30 days prior to tumor cell inoculation and sinse the 1st day of inoculation. Mice taking destilled mineralized water were considered as a control group. Half of the mice were injected melanoma B16 cells subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Interesting, several in vitro studies suggested that water with a low deuterium concentration (<65 ppm) may inhibit cancer growth ( 221 229 ) and augments the inhibitory effect of paclitaxel ( 230 ). Anecdotal reports and clinical data from Europe suggest that lowering the levels of deuterium in the body by drinking deuterium depleted water (10-20 ppm) may improve quality of life and possibly survival of cancer patients ( 231 233 ).…”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…Interesting, several in vitro studies suggested that water with a low deuterium concentration (<65 ppm) may inhibit cancer growth ( 221 229 ) and augments the inhibitory effect of paclitaxel ( 230 ). Anecdotal reports and clinical data from Europe suggest that lowering the levels of deuterium in the body by drinking deuterium depleted water (10-20 ppm) may improve quality of life and possibly survival of cancer patients ( 231 233 ).…”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…Shifts in the deuterium body content have been shown to be easily achieved by the substitution of drinking water by deuterium-depleted or deuterium-enriched water, a simple and safe method [ 9 ]. The administration of deuterium-depleted water has been shown to improve the results of antitumor treatment and has been recommended as a supplemental treatment for chemotherapy [ 3 , 10 ]. As the beneficial effects of deuterium-depleted water resulted from the better function of mitochondrial oxidation, deuterium reduction has potentially become a promising tool in the treatment of metabolic disorders [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of knowledge on deuterium function complicates the prediction and assessment of physiological changes induced by shifts in the deuterium/protium balance. It has been found that the consumption of deuterium-depleted water from the day of inoculation of tumor cells does not affect tumor growth and metastasis in mice, whereas preliminary deuterium depletion significantly reduces tumor growth and increases survival rate [ 10 ]. These results suggest that shifts in the deuterium body content affect metabolic patterns and alter organ physiology, and that development of physiological changes depends on the time and amplitude of the deuterium/protium disbalance.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a change in the deuterium content of living systems affects their metabolic processes [2,3]. This applies to both elevated [4] and reduced deuterium concentrations relative to the natural level [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%